Identity Crisis

Geometry Level pending

Consider c o s ( β ) = 4 5 cos\left( -\beta \right) =\frac { 4 }{ 5 } , where β -\beta is in the fourth quadrant. Find the value of s i n ( 3 β 4 ) + s i n ( β 4 ) c o s ( 3 β 4 ) + c o s ( β 4 ) \frac { sin\left( \frac { 3\beta }{ 4 } \right) +sin\left( \frac { \beta }{ 4 } \right) }{ cos\left( \frac { 3\beta }{ 4 } \right) +cos\left( \frac { \beta }{ 4 } \right) }


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Lui Banzon
Nov 15, 2014

Using a sum-to-product identity,

s i n ( 3 β 4 ) + s i n ( β 4 ) c o s ( 3 β 4 ) + c o s ( β 4 ) = 2 s i n ( 3 β 4 + β 4 2 ) c o s ( 3 β 4 β 4 2 ) 2 c o s ( 3 β 4 + β 4 2 ) c o s ( 3 β 4 β 4 2 ) = s i n ( β 2 ) c o s ( β 2 ) = t a n ( β 2 ) = c o s ( β ) + 1 s i n ( β ) \frac { sin\left( \frac { 3\beta }{ 4 } \right) +sin\left( \frac { \beta }{ 4 } \right) }{ cos\left( \frac { 3\beta }{ 4 } \right) +cos\left( \frac { \beta }{ 4 } \right) } \qquad =\qquad \frac { 2sin\left( \frac { \frac { 3\beta }{ 4 } +\frac { \beta }{ 4 } }{ 2 } \right) cos\left( \frac { \frac { 3\beta }{ 4 } -\frac { \beta }{ 4 } }{ 2 } \right) }{ 2cos\left( \frac { \frac { 3\beta }{ 4 } +\frac { \beta }{ 4 } }{ 2 } \right) cos\left( \frac { \frac { 3\beta }{ 4 } -\frac { \beta }{ 4 } }{ 2 } \right) } \\ \qquad \qquad \qquad \qquad =\qquad \frac { sin\left( \frac { \beta }{ 2 } \right) }{ cos\left( \frac { \beta }{ 2 } \right) } \\ \qquad \qquad \qquad \qquad =\qquad tan\left( \frac { \beta }{ 2 } \right) \\ \qquad \qquad \qquad \qquad =\qquad \frac { cos\left( \beta \right) +1 }{ sin\left( \beta \right) }

Since y = c o s ( x ) y = cos\left( x \right) is an even function, c o s ( β ) = c o s ( β ) cos\left( -\beta \right) =cos\left( \beta \right) . Solving for s i n ( β ) sin\left( \beta \right) and plugging in the values,

= 4 5 + 1 3 5 = 3 \qquad \qquad \qquad \qquad =\qquad \frac { \frac { 4 }{ 5 } +1 }{ \frac { 3 }{ 5 } } \\ \qquad \qquad \qquad \qquad =\qquad 3

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...